Instrument and measurement automation for classical control of a multi-qubit quantum processor - KRIŽAN, CHRISTIAN (My University, 2019)
The recent field of quantum computing has seen great progress in the development of multi-qubit systems, with qubit usability lifetimes increasing, putting practical quantum computers on the near-horizon. As these systems take shape, scalability becomes of high priority as implementable algorithms require a multitude of qubits to function. Such systems will require precise timing control using instrument platforms for their development to continue. In this thesis, I develop and present such an instrument platform solution. This platform consists of automated instrument drivers written for Zurich Instruments’ HDAWG arbitrary waveform generator and UHFQA lockin amplifier i.e. classical electronic control systems. The drivers are integrated in the experimentcontrol software Labber, and verified by characterising a multi-qubit quantum processor loaded with a two-qubit DUT. One qubit is further characterised using the drivers, with extracted values of interest including: the qubit frequency, f01, located at 4.302665 GHz ± 3.916MHz; the -pulse amplitude, , of 721mV ± 20mV; and the energy relaxation time, T1, of ~57.6 μs. The platform is then benchmarked in terms of duration times for typical events in a running experiment, such as Labber-to-instrument connection times (2 603 ms and 2 328 ms for the UHFQA and HDAWG respectively), compilation times (632 ms and 1 288 ms), and finally also waveform data upload times to the instruments (764 ms and 1 481 ms). The platform control was optimised in terms of upload speed, using a memory injection technique for the HDAWG. The upload time was reduced to 131 ms, typically demonstrating an averaged improvement of >91% (131 ms vs. 1 481 ms). Finally, I discuss some observed potential for improvement, and speculate as to the onwards outlook regarding the future of the delivered instrument automation platform.
Keywords: quantum; processor; superconducting; Python; spectroscopy; Bloch; qubit; resonator; dispersive; Rabi